Fosfato decantado e calagem no perfilhamento e produção de massa seca do capim-marandu - Leal, Fábio Tiraboschi [UNESP] (2015)
The decanted phosphate (DF), by-product of wastewater treatment of phosphoric acid production (H3PO4), is considered an environmental liability and resulting economic obligations to the phosphate fertilizer manufacturers. In this sense, this experiment was conducted in a greenhouse using pots filled with samples of a sandy clay loam Typic Haplustox with main objective to evaluate the effects of DF at tillering and shoot dry matter production of marandu grass (Brachiaria brizantha cv. Marandu) during three consecutive growths in the presence and absence of lime. The experiment was conducted in a completely randomized experimental design with three replications, according to a factorial 6 x 2 x 2 [six rates of P; two sources of P; presence (P/L) and absence of lime (A/L)]. The rates of P were 0, 30, 60, 90, 120 and 150 mg kg-1 of P. The sources of P were the DF and triple superphosphate (TS) (reference source). Lime was applied to the soil in an amount calculated to raise the soil base saturation to 60%. It was found that the phosphate fertilization caused a significant increase in tillers number and shoot dry matter of marandu grass, and the DF did not differ significantly from the TS in the absence of lime, but was significantly lower in the presence of this correction. P supply to the soil by FD was favored by soil acidity which was increased in the course of the experiment The critical levels of P in soil and the marandu grass shoot were 15 mg dm-3 and 1.2 g kg-1, respectively